Relationship between antithymocyte globulin, T cell phenotypes, and clinical outcomes in pediatric kidney transplantation. Issue 2 (12th September 2020) - Shaw, Brian I.; Lee, Hui‐Jie; Chan, Cliburn; Ettenger, Robert; Grimm, Paul; Pearl, Meghan; Reed, Elaine F.; Robien, Mark A.; Sarwal, Minnie; Stempora, Linda; Warshaw, Barry; Zhao, Congwen; et al.
Abstract : Depletional induction using antithymocyte globulin (ATG) reduces rates of acute rejection in adult kidney transplant recipients, yet little is known about its effects in children. Using a longitudinal cohort of 103 patients in the Immune Development in Pediatric Transplant (IMPACT) study, we compared T cell phenotypes after ATG or non‐ATG induction. We examined the effects of ATG on the early clinical outcomes of alloimmune events (development of de novo donor specific antibody and/or biopsy proven rejection) and infection events (viremia/viral infections). Long‐term patient and graft outcomes were examined using the Scientific Registry of Transplant Recipients. After ATG induction, although absolute counts of CD4 and CD8 T cells were lower, patients had higher percentages of CD4 and CD8 memory T cells with a concomitant decrease in frequency of naïve T cells compared to non‐ATG induction. In adjusted and unadjusted models, ATG induction was associated with increased early event‐free survival, with no difference in long‐term patient or allograft survival. Decreased CD4 + naïve and increased CD4 + effector memory T cell frequencies were associated with improved clinical outcomes. Though immunologic parameters are drastically altered with ATG induction, long‐term clinical benefits remain unclear in pediatric patients. Abstract : The authors identify an association between antithymocyte globulin–based induction, an increase in memory and mature T cell phenotypes, and improved short‐term but not long‐term clinical outcomes for children undergoing kidney transplantation.